Effect of different levels of NPKS and rhizobium inoculation on growth, yield attributes of soyabean (Glycine max) under guava (Psidium guajava) based agrihorticulture system - pandey, Ankit (Indian Journal of Agroforestry, 2023)
The present study was carried out to study the “Effect of different levels of NPK and S, on growth, and yield of soybean (Glycine max L. Merrill) under guava (Psidium guajava L.) based Agri-Horticulture system” in the agriculture research farm of Rajiv Gandhi South Campus, Banaras Hindu University Barkachha Mirzapur Uttar Pradesh. Soybean was a major crop grown in agroforestry systems. A study was carried out during (Kharif) rainy season 2018-19 in a 12- year-old guava based Agri-Horti system with five treatments viz., T1 Control (no fertilizer), T2 (N: 20 kg, P2O5: 40 kg,  K2O: 30 kg, and S: 10 kg ha-1), T3 (N: 30 kg, P2O5, K2O: 40 kg, and S: 20 kg ha-1 ), T4 (N: 40 kg, P2O5: 80 kg, K2O: 50 kg, and S: 30 kg ha-1), T5 (N: 50 kg, P2O5: 100 kg, K2O: 60 kg, S: 40 kg ha-1 ) respectively, and every treatment was replicated four times in Complete Randomized Block Design. The results reveal that the maximum growth and yield of soybean recorded with T5 N (50 kg ha-1) + P2O5 (100 kg ha-1) + K2O (60 kg ha-1) + S (40 kg ha-1), and the minimum was observed with T1 (Control).